Penerapan Model Inkuiri Terbimbing terhadap Hasil Belajar Siswa Materi Pesawat Sederhana pada Siswa SMP - Diyah Rahmawati; Arini Rosa Sinensis; Effendi Effendi (U-Teach: Journal Education of Young Physics Teacher, 2023)
This research aims to: 1) find out how the application of the guided inquiry learning model to student learning outcomes. 2) analyze the improvement of the guided inquiry learning model on student learning outcomes, and 3) determine the effect of the guided inquiry learning model on student learning outcomes. The type of research used in this study is quasi-experiment, the design used in this study is prestest-postest control group design. This study used an initial test before treatment (prestest) and a final test after treatment (postest). Data collection in this study used test questions in the form of multiple choice. The application of guided inquiry begins with an initial test (prestest) before being given treatment then continued with the learning process on simple aircraft material and after learning a final test (postest) of student learning results is carried out. The results showed that there was an increase in student learning outcomes on average scores after treatment in each class was obtained by 77.66 in the experimental class while in the control class by 72.07. From the average N-Gain value of the experimental class was 0.47 while in the control class 0.37. The average N-Gain score category in both classes is medium. So from the results of the data collected using the t-test at a significant level α = 0.05. From the results of data processing, it turns out that the tcount > table is 2.17>2.00 so that Ho is rejected and Ha is accepted. This study shows that there is a significant influence of guided inquiry learning models on student learning outcomes